Group Guidance Effectiveness through Bibliotherapy to Reduce Academic Anxiety - Olivia Sriferina; Alizamar Alizamar; Marjohan Marjohan (Journal of Educational and Learning Studies, 2019)
Academic anxiety experienced by students in the teaching and learning process in schools often inhibits learning achievement optimally even though various counseling, students should be able to develop the potential within themselves without worrying, but here there are many students who cannot explore the potential within themselves so that academic anxiety occurs. for that we need a group guidance service using the bibliotherapy method. This study aims to examine the effectiveness of group guidance services through bibliotherapy to reduce students' academic anxiety. The research methodology used was quasi experiment. The subjects of this study were 8 grade students of MTsN 6 & MTsN 2 Padang with 10 subjects in the experimental group and 10 in the control group. The research instrument used instrument of academic anxiety. The results showed that there were significant differences in the academic anxiety of the experimental group before (pretest) and after (posttest) taking group guidance services with bibliotherapy and could not have a significant difference in the control group's academic anxiety before (pretest) and after (posttest). The implications of this study are as a basis for counselors to reduce students' academic anxiety.